From West-East knowledge transfer to effective working relationships: Lessons from Commercial Capital S. A. - Paul R. Lawrence; Charalambos A. Vlachoutsicos; Snejina Michailova (Journal for East European Management Studies, 2005)
In the process of investing and managing in former Soviet-bloc transition countries, Westerners are exposed to important gaps that must be bridged. Over the last fifteen years and partly through trial and error, CC has developed a comprehensive approach for planning, establishing and managing their investments in these countries by linking mission, goals, organizational structure and organizational culture as components of their overall investment strategy. – – Im Laufe des Prozesses der Investionen und des Managements in den früheren Ostblockstaaten sehen die Menschen aus dem Westen sich vielen Schwierigkeiten gegenüber, die es zu beseitigen gilt. In den letzten 15 Jahren und teilweise durch Trial and Error hat Commercial Capital eine umfassende Herangehensweise entwickelt, zur Planung, Entwicklung und Leitung von Investitionen in diesen Ländern mithilfe der Verbindung von Aufgaben, Zielen, der Organisationsstruktur und Organisationskultur als Komponenten einer übergeordneten Investitionsstrategie.
Keywords: 650; Transition countries; Western managers; locals; cooperation business models